Stabilization of Cox1p intermediates by the Cox14p–Coa3p complex. Issue 7 (19th February 2013) - McStay, Gavin P.; Su, Chen Hsien; Tzagoloff, Alexander
Abstract : Cox14p and Coa3p have been shown to regulate translation of the mitochondrial COX1 mRNA and to be required for assembly of cytochrome oxidase. We present evidence that Cox14p and Coa3p stabilize previously identified Cox1p intermediates and that in the absence of either protein, Cox1p aggregates with itself and other mitochondrial gene products, including cytochrome b, Var1p and Cox2p. Our evidence suggests that Cox1p assembly intermediates are in close proximity to other mitochondrially translated proteins and that an important function of Cox14p and Coa3p is to prevent Cox1 from entering into unproductive aggregation pathways. Abstract : ► Coa3p is associated with the same four Cox1p assembly intermediates as Cox14p. ► Cox14p and Coa3p stabilize four Cox1p assembly intermediates. ► Cox1p aggregates with other mitochondrial gene products in cox14 or coa3 mutants. ► Aggregated Cox1p is incompetent in assembling into cytochrome oxidase. ► Some newly translated mitochondrial gene products are proximate in the membrane.